Thromboprophylaxis after major orthopedic surgery: Improving compliance with clinical practice guidelines (2016)
Introduction Identifying risk factors and strategies for the prevention of deep venous thromboembolism in major orthopedic surgery has allowed the development of Clinical Practice Guidelines (CPGs). Currently, there is a gap between clinical practice and the implementation of the recommendations of CPGs. The purpose of this paper is to report the impact of the implementation of improvement strategies on adherence to venous thromboembolism (VTE) prophylaxis guidelines. Materials and methods We defined 3 quality indicators to assess the adequate use of thromboprophylaxis according to CPGs. We obtained a baseline measurement and identified several barriers for adherence. Six improvement strategies to promote adherence to CPGs were designed and applied. A systematic monitoring of these indicators was performed in real time and a description of the data was completed for patients undergoing primary joint replacement of the hip, knee and shoulder, during February 2012 and August 2014. Results Data from 773 patients were obtained. In the first trimester, the average of adherence was: 98.3% for medical order in the post-operative note, 60.3% for opportune administration and 67% for adherence to therapy at home. In the trimester, the rates of adherence were 100%, 95.7% and 100% respectively. Conclusions Combined strategies for improvement of adherence to VTE prophylaxis is associated with higher compliance with clinical practice guidelines. © 2015 Published by Elsevier Ltd.